OBSERVATION OF D,E AND DELTA-MESONS IN PI-P-INTERACTIONS AT 12 AND 15 GEV-C - Corden, M; Dowell, J; Garvey, J; Jobes, M; Kenyon, I; Mawson, J; Mcmahon, T; Corbett, I; Esterling, R; Lipman, N; Litchfield, P; Sumorok, K; et al. (1978)
We have observed the D(1285), E(1420) and δ(975) mesons produced in 12 and 15 GeV/c π-p interactions at the CERN Omega Spectrometer. Production cross sections and decay branching ratios are presented. Analysis of the decay D(1285) → δ(975) π favours a spin-parity assignment of 1+. © 1978.